Improvement and Prediction of Memory and Executive Functions in Patients Admitted to a Neurosurgery Service With Complicated and Uncomplicated Mild Traumatic Brain Injury. Issue 5 (September 2019) - Holthe, Oyvor Oistensen; Hellstrom, Torgeir; Andelic, Nada; Server, Andres; Sigurdardottir, Solrun
Abstract : Objectives: To compare neuropsychological performances between patients with and without intracranial abnormalities after mild traumatic brain injury (mTBI) and assess the relationship between demographics, injury severity, and self-reported symptom characteristics with improvements in memory and executive functions (8 weeks to 1 year postinjury). Setting: Inpatient/outpatient followed up at the Department of Physical Medicine and Rehabilitation, Oslo, Norway. Participants: Patients were divided into groups of complicated ( n = 73) or uncomplicated mTBIs ( n = 77) based on intracranial findings on computed tomographic or magnetic resonance imaging brain scans. Design: Prospective, longitudinal cohort study. Main Measures: Neuropsychological assessments of memory and executive functions, self-reports of postconcussion, depression, posttraumatic stress symptoms, and general functioning at 8 weeks and 1 year postinjury. Results: Longitudinal data showed that patients with complicated and uncomplicated mTBIs had similar cognitive performance and improvements. Hierarchical linear modeling revealed that individuals with early posttraumatic stress disorder and/or depressive symptoms performed worse on measures of Memory functions, and those with younger age (<40 years) and lower education (<12 years) performed worse on measures of Executive functions. Conclusion: Findings are suggestive of a good cognitive outcome following complicated and uncomplicated mTBIs. Early assessments of posttraumatic stress disorder and depression seem useful in identifying those most vulnerable having poorer cognitive outcomes, providing further interventions that may affect emotional and cognitive recovery. Abstract : Supplemental Digital Content is Available in the Text.